Contact Lens–Induced Discomfort and Inflammatory Mediator Changes in Tears. Issue 1 (January 2017) - Masoudi, Simin; Zhao, Zhenjun; Stapleton, Fiona; Willcox, Mark
Abstract : Purpose: Studies indicate that contact lens (CL) discontinuation mostly occurs because of dryness and discomfort symptoms. This study aimed to investigate relationships between changes in the concentration of tear inflammatory mediators with subjective comfort ratings with CL wear and no contact lens wear between morning and evening. Method: Forty-five subjects collected tears twice daily in the morning and in the evening with or without lenses. Comfort was rated subjectively on a scale from 1 to 100 (where 100 was extremely comfortable) just before each tear collection. Tear samples were assayed for complement components (C3 and C3a ), leukotriene B4 (LTB4 ), secretory phospholipase A2 (sPLA2 ), secretory immunoglobulin A (sIgA), and bradykinin using commercially available immuno-based assay kits. Results: Comfort ratings showed a statistically significant decline from morning to evening both with CL (89.0±10.1 AM vs. 76.7±15.2 PM; P <0.001) and without CL (89.1±10.2 AM vs. 84.2±12.6 PM; P <0.005) wear. The decline was steeper with lens wear ( P <0.001). Bradykinin and sPLA2 levels did not change between morning and evening or with CL wear ( P >0.05). Leukotriene B4 levels were slightly higher in CL (CL 43.4±12.6 pg/ml vs. No CL 39.4±13.4 pg/mL; P =0.034), whereas the concentration of LTB4, C3, C3a, and sIgA dropped by the end of the day in the presence or absence of lens wear ( P <0.001). For most mediators, tear levels were not correlated with comfort ratings in any of the conditions. Leukotriene B4 had a higher concentration in the evening, and when measured as a ratio to sIgA, there was a trend for increased concentration of this mediator during CL wear. Conclusion: Although specific mediators showed changes from morning to evening with and without lens wear, most of these were not correlated with subjective comfort ratings in lens wear. The only mediator that showed an increase in concentration during the day and during lens wear was LTB4, and further studies on this mediator are warranted.